2013
DOI: 10.11646/zootaxa.3648.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Some shallow-water hydroids (Cnidaria: Hydrozoa) from the central east coast of Florida, USA

Abstract: This paper gives a systematic account of 67 species, referable to 22 families and 40 genera, identified in a small collection of hydroids from the central Atlantic coast of Florida between Melbourne and Palm Beach. The fauna mostly comprises an assemblage of tropical western Atlantic species ranging northwards along the southeastern coast of the United States. One new species, Lafoea intorta, is described. Applying Reversal of Precedence provisions in zoological nomenclature, the widely-used generic name Halop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 145 publications
1
28
0
Order By: Relevance
“…monosiphonic stem (similar to other Gymnangium ) but elongated hydrotheca, not bent or folded, without abcauline intrathecal septum (resembling Taxella ). Because the present 16S data as well as an earlier analysis of Postaire et al [33] clearly indicate a polyphyly of the genus Gymnangium sensu Bouillon et al [4] we prefer to separate the Gymnangium species of Clade A into a different genus, and for which there is conveniently already a name available, Taxella Allman, 1874.…”
Section: Resultsmentioning
confidence: 62%
“…monosiphonic stem (similar to other Gymnangium ) but elongated hydrotheca, not bent or folded, without abcauline intrathecal septum (resembling Taxella ). Because the present 16S data as well as an earlier analysis of Postaire et al [33] clearly indicate a polyphyly of the genus Gymnangium sensu Bouillon et al [4] we prefer to separate the Gymnangium species of Clade A into a different genus, and for which there is conveniently already a name available, Taxella Allman, 1874.…”
Section: Resultsmentioning
confidence: 62%
“…Detailed information also appeared in the monograph on gymnoblastic hydroids by Allman (1872: 223-226 and 290-292, as Gemmaria implexa). A contemporary synonymy of Z. implexa is given in , and the nomenclatural status of the genus name Zanclea has been discussed earlier (Calder , 1992(Calder , 2013. According to Cornelius & Garfath (1980), syntype material of the species exists at the Hancock Museum (now the Great North Museum: Hancock), Newcastle-upon-Tyne, England.…”
Section: Reports Of Hydroids From the East Coast Of North America Datmentioning
confidence: 99%
“…Even knowledge of hydrozoan species in this area remains at a basic level and is incomplete due to a lack of general interest in studying the science of taxonomy and systematics. However, P. porpita can be carried to the Bangladesh coast by strong southwest monsoon winds, as observed in other places (see Calder 2013). In addition, their occurrence may be related to higher water temperature and salinity resulting from global warming (Edwards and Richardson 2004;Richardson and Schoeman 2004;Oiso et al 2005), but the detailed mechanism involved has not been identified.…”
Section: Discussionmentioning
confidence: 93%